CHOICES OF WORDS IN WRITING: A CASE STUDY AMONG EXTROVERT AND INTROVERT - Zainal, Lina; Mohamad, Maslawati (ZES ROKMAN RESOURCES, 2020)
Studies have been conducted on personality and writing in the contexts of the second language. Most learners are not aware that their personality is present in their writing based on their choices of words. Hence, it has sparked the interest of many scholars to seek more knowledge in this matter. Although many studies have been conducted to study the presence of personality influence in L2 learners, little is known about how personality affect L2 writing. It includes the type of writing, the type of words chosen and the way L2 learning style would affect how learners perform in their writing. The objectives of this paper is to find out the type of personality traits possess by the participants and to explore how personality traits influences their choices of words in writing. The study adapted qualitative research method as it is a case study among two female participants in a higher learning institution in Malaysia. The participants writing documents were analysed using content analysis based on the 3 different categories determined by the researcher. The findings revealed that the most common categories occurred in their writing are ‘self-reference words’, ‘positive emotions words’ and ‘negative emotions words’. The findings of this study showed that the introvert participant constantly use more words in all categories. Thus it indicates influence of the introvert’s natural characteristics in her writing due to the fact she is comfortable expressing herself without the influence of outside world. She also found to be more expressive in writing compared to the extrovert.